The Dynamics of Public Sphere in Social Media: Cybermedia Analysis - Petrus Ana Andung; Maria Via Dolora Pabha Swan (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
Social media use in Indonesian society has increased rapidly. One of the Facebook groups formed by the netizens of Nusa Tenggara Timur (NTT), who actively build virtual discussions, is the NTT Baru Facebook Group with 86,783 followers. This article aims to analyze the public sphere dynamics that occur in this Facebook group. This qualitative approach used cybermedia analysis methods. The results showed that the Facebook group was a forum for NTT netizens to virtually gather and freely discussing public service issues in NTT Province. The Group was a virtual public space for NTT netizens to demonstrate democratic practices to reflect civil society’s increasing control function. The Group’s existence was used as a political communication instrument in building social mobilization and as moral and political support for the governor and deputy governor of NTT, Viktor Laiskodat and Josef Nae Soi.